Sosialisasi Pembuatan Pupuk Organik dari Limbah Organik Rumah Tangga Berbantu Compost Bag - Setiawan, Oki; Pambudiarto, Benny Arif; Purwaningtyas, Fiska Yohana; Mustikaningrum, Mega; Aghata, Esteranita Betzy; Fatmawati, Yuni (Jurnal Pengabdian Masyarakat dan Lingkungan (JPML), 2025)
Household waste has become a pressing issue that needs to be addressed immediately, starting from the household level. Integrated solutions for household waste management have been implemented, both in the form of local regulations and direct socialization of household waste management to residents. However, optimization has not yet been achieved due to the increasing amount of household waste each year. One of the contributions from universities is to provide socialization and training on household waste management, covering materials on the sorting of organic and inorganic waste, the making of organic fertilizer for the community, the dissemination of organic fertilizer use, and an explanation of the impacts of poorly managed waste from an environmental perspective. The program implemented in this community service is the socialization of organic fertilizer making assisted by compost bags in Kedanyang Village, Gresik. Organic fertilizer made using compost bags is rich in carbon and nitrogen compounds, which are good for plant growth. This socialization also aims to reduce the impact of waste disposal on the environment, such as soil, water, and air pollution, and its effects on human health. In this compost bag method, the basic materials are dry and wet waste in a certain ratio, assisted by EM4 activator so that the composting process can run better. Organic fertilizer is made within 3-4 weeks before use and is in solid form.